The effects of age stereotypes on physical and mental health are mediated by self-perceptions of aging - Brothers, Allyson; Kornadt, Anna E.; Nehrkorn-Bailey, Abigail; Wahl, Hans-Werner; Diehl, Manfred (The journals of gerontology. Series B, Psychological sciences, social sciences, 2021)
Objectives. Although the evidence linking Views on Aging (VoA) with aging outcomes is robust, little is known about how different types of VoA may interact to influence such outcomes. Therefore, this study examined two types of VoA, Age Stereotypes (AS), representing general VoA, and Self-Perceptions of Aging (SPA), representing personal VoA. We operationalized SPA in terms of Awareness of Age-Related Change (AARC), distinguishing between gain- and loss-related SPA (e.g., awareness of positive and negative age-related changes, respectively). Based on theoretical reasoning, we hypothesized that AS would be an antecedent of SPA, and that the effect of AS on physical and mental health would be mediated by SPA.